Peru : Recent Economic Developments. (IMF Staff Country Reports; Country Report, 1996)
This paper describes economic developments in Peru during the 1990s. During 1990-92, real GDP growth was negative by 0.9 percent a year on average, reflecting in part deterioration in the terms of trade and adverse weather conditions. During that period, growth in the construction, manufacturing, and fishing sectors was more than offset by a contraction in the agricultural and mining sectors. Gross domestic investment rose from about 15 1\2 percent of GDP in 1990 to 16 1\2 percent in 1992 mainly on the strength of public sector investment.